menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
3(x-6)-8x = -2+5(2x+1)
asked
Jun 5, 2021
143
views
1
vote
3(x-6)-8x = -2+5(2x+1)
Mathematics
middle-school
Andrew Lewis
asked
by
Andrew Lewis
4.9k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
4
votes
Not 100% sure if this is correct but the answer is X=-7/5.
Justus
answered
Jun 10, 2021
by
Justus
5.4k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.9m
questions
7.7m
answers
Other Questions
Solve for y in terms of x. 2/3y - 4 = x y = x + 6 y = -x + 4 y = -x + 6 y = x + 4
Aliyah has $24 to spend on seven pencils. After buying them she had $10. How much did each pencil cost?
Use the normal model n(11371137,9696) for the weights of steers. a) what weight represents the 3737thth percentile? b) what weight represents the 9999thth percentile? c) what's the iqr of the weights
Evaluate a + b when a = –16.2 and b = –11.4 A. –27.6 B. –4.8 C. 4.8 D. 27.6
What is the value of x? (-4) - x = 5
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org